Critical review on the chemical reduction of nitroaniline. Issue 32 (19th May 2020) - Din, Muhammad Imran; Khalid, Rida; Hussain, Zaib; Najeeb, Jawayria; Sahrif, Ahsan; Intisar, Azeem; Ahmed, Ejaz
Abstract : Schematic illustration of catalytic reduction of 4-NA in the presence of nanocatalysts and a reducing agent. Abstract : Conversion of nitroaniline (NA), a highly toxic pollutant that has been released into aquatic systems due to unmanaged industrial development in recent years, into the less harmful or a useful counterpart is the need of the hour. Various methods for its conversion and removal have been explored. Owing to its nominal features of advanced effectiveness, the chemical reduction of 4-NA using various different nanocatalytic systems is one such approach that has attracted tremendous interest over the past few years. The academic literature has been confined to case studies involving silver (Ag) and gold (Au) nanoparticles, as these are the two most widely used materials for the synthesis of nanocatalytic assemblies. Focus has also been given to sodium borohydride (NaBH4 ), which is used as a reductant during the chemical reduction of NA. This systematic review summarizes the fundamentals associated with the catalytic degradation of 4-NA, and presents a comprehensive and critical study of the latest modifications used in the synthesis of these catalytic systems. In addition, the kinetics, mechanisms, thermodynamics, as well as the future directions required for understanding this model reaction, have been provided in this particular study.